2019
DOI: 10.1101/778795
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular characterization of carbapenem-resistant Klebsiella pneumoniae isolates with focus on antimicrobial resistance

Abstract: 19The enhancing incidence of carbapenem-resistant Klebsiella pneumoniae (CRKP)-mediated 20 infections in Mengchao Hepatobiliary Hospital of Fujian Medical University in 2017 is the 21 motivation behind this investigation to study gene phenotypes and resistance-associated genes of 22 emergence regarding the CRKP strains. In current study, seven inpatients are enrolled in the 23 hospital with complete treatments. The carbapenem-resistant K. pneumoniae whole genome is 24 sequenced using MiSeq short-read and Oxfor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
2
4
0
1
Order By: Relevance
“…The coexistence of carbapenemase and ESBL was found in 18 isolates. The high incidence (67%) of isolates with coexpression of carbapenemase and ESBL found in this study has also been noted in previous studies from Tunisia and other parts of the world (Uz Zaman et al 2014;Loucif et al 2016;Yu et al 2019;Messaoudi et al 2020;Sharahi et al 2021).…”
Section: Phenotypic and Genotypic Profiles Of Carbapenemresistant Iso...supporting
confidence: 89%
“…The coexistence of carbapenemase and ESBL was found in 18 isolates. The high incidence (67%) of isolates with coexpression of carbapenemase and ESBL found in this study has also been noted in previous studies from Tunisia and other parts of the world (Uz Zaman et al 2014;Loucif et al 2016;Yu et al 2019;Messaoudi et al 2020;Sharahi et al 2021).…”
Section: Phenotypic and Genotypic Profiles Of Carbapenemresistant Iso...supporting
confidence: 89%
“…We also found that all ST15 CRKP isolates carried the gene oqxAB encoding the quinolone efflux pump and the phosphomycin resistance gene fosA [14]. According to previous studies, oqxAB encodes the efflux pump responsible for quinolone resistance, but it cannot be excluded that cephalosporins, carbapenems, and other antibiotics are pumped from the K. pneumoniae cell membrane through this efflux pump [15], while fosA may be widespread in gram-negative bacteria, which is consistent with previous studies [16]. Also tetracycline resistance gene tet(A) (92%), aminoglycoside resistance genes aac(3)-lid (100%) and aac(6')-lb-cr (69%).…”
Section: Antibiotic Resistance Genes (Args)mentioning
confidence: 71%
“…1a, b. A rational design approach has been applied to the putative Komodo dragon cathelicidin sequences in order to generate a series of novel synthetic peptide derivatives(Table 1).Carbapenem-resistant Klebsiella pneumonia (CRKP) is often highly resistant to multiple antibiotics including all betalactams, fluoroquinolones and aminoglycosides[35]. To investigate the ability of a library of novel, synthetic antimicrobial peptides against carbapenem-resistant Klebsiella pneumonia, we performed MIC assays according to CLSI standards.…”
mentioning
confidence: 99%